2019
DOI: 10.1097/bpo.0000000000001468
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Mobile Application for Measuring Femoral Anteversion in Patients With Cerebral Palsy

Abstract: Background: Computed tomography (CT) provides benefits for 3-dimensional (3D) visualization of femur deformities. However, the potential adverse effects of radiation exposure have become a concern. Consequently, a biplanar imaging system EOS has been proposed to enable reconstruction of the 3D model of the femur. However, this system requires a calibrated apparatus, the cost of which is high, and the area occupied by it is substantial. The purpose of this study was to develop a mobile application t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Limb-alignment MRI protocols have been developed which have decreased exam time requirements, though the relative cost of an MRI remains a significant consideration in the US healthcare system [ 46 , 57 ]. Sung et al developed and validated a mobile application that can reliably measure femoral anteversion from AP and lateral femur radiographs [ 58 ]. In an MRI study comparing a population of patients with recurrent patellar dislocations and controls, Maine et al quantified the rotational alignment of the extensor mechanism, known as the quadriceps torsion angle (QTA).…”
Section: Imagingmentioning
confidence: 99%
“…Limb-alignment MRI protocols have been developed which have decreased exam time requirements, though the relative cost of an MRI remains a significant consideration in the US healthcare system [ 46 , 57 ]. Sung et al developed and validated a mobile application that can reliably measure femoral anteversion from AP and lateral femur radiographs [ 58 ]. In an MRI study comparing a population of patients with recurrent patellar dislocations and controls, Maine et al quantified the rotational alignment of the extensor mechanism, known as the quadriceps torsion angle (QTA).…”
Section: Imagingmentioning
confidence: 99%
“…A lot of authors think that 2D-CT method is to use 2D images to measure the 3D structure, which is obviously inaccurate, as 2D images cannot simultaneously show the complete structure of the proximal femur [ 29 , 30 ]. Besides, in 2D-CT measurement method, it is more random and subjective in selection of CT slice images for measurement, which leads to great differences in measurement results between different physicians [ 31 , 32 ]. In this study, it is found that the difference in results between 3D-PF model and 2D-CT measurement was statistically significant, indicating that the accuracy of 2D-CT measurement method was not very good.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of authors think that 2D-CT method is to use 2D images to measure the 3D structure, which is obviously inaccurate, as 2D images cannot simultaneously show the complete structure of the proximal femur [26]. Besides, in 2D-CT measurement method, it is more random and subjective in selection of CT slice images for measurement, which leads to great differences in measurement results between different physicians [27,28]. In this study, it is found that the difference in results between 3D-PF model and 2D-CT measurement was statistically signi cant, indicating that the accuracy of 2D-CT measurement method was not very well.…”
Section: Discussionmentioning
confidence: 99%